PERAN PELAYANAN BERBASIS ABILITY DAN LOYALITY TERHADAP PERBAIKAN KUALITAS PELAYANAN TENAGA KEPENDIDIKAN DI STBA JIA BEKASI TAHUN 2019 - Ahmad Kurnia; Ade Surista (STBA JIA Press, 2020)
This study aims to identify and explain how much influence the effect of ability, and loyalty to quality service of education staft in STBA JIA in Bekasi. This research is an ex-post facto nature of causality. The population in this study is education staft in the District of Bekasi. The study population 21 staft and 16 education staft sample taken using quota random sampling. The instrument used consisted of ability questionnaire, questionnaire loyalty, and service quality. Data were analyzed with descriptive statistics and inferential statistical analysis (multiple regretion analysis). The results showed that 1) Variable of ability direct positive effect on quality service of education staft. 2) loyalty direct positive effect on quality service 3) ability and loyalty direct positive effect simultant on qualiy service.